Study of coastal land change in sand mining activities in Bandar Batauga Village, South Buton Regency, Indonesia - Mappasomba, Zulkifli; Suleman, Romiyatno (Journal of Degraded and Mining Lands Management, 2024)
This research focused on land changes in Bandar Batauga Village, South Buton Regency, Indonesia, related to environmentally damaging sand mining activities. The primary objective of this research was to analyze land evolution in coastal settlement areas vulnerable to disasters, with an emphasis on the impact of sand mining until the year 2050. The research methods encompassed quantitative and qualitative approaches, including coastal change analysis using ArcGIS, in-depth interviews, and statistical methods. The research findings highlighted a significant increase in coastline changes, reaching an erosion area of 511.3 m² in 2022. Projections until 2050 indicate a potential maximum erosion of 1,157.22 m². This research employed the analytic hierarchy process, focusing on social, economic, physical, and biotic environmental aspects to formulate disaster mitigation strategies. However, implementing environmental management policies faces challenges, such as a lack of competence in relevant departments and low awareness among mining permit owners. Therefore, strategic recommendations involve enhancing human resource capacity, strengthening oversight, and providing economic support as critical steps to reduce mining activities.